Development and feasibility of an educational intervention to improve participation for people with spinal cord injury from Gaza, Palestine - Abu Mostafa, Moussa Kleib (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.